Recent Advances in Educational Planning: Theory, Implementation, and Visions of the Future by Philip H. Coombs - Marlina, Elvia Hani; Suyatman, Ujang (UIN Sunan Gunung Djati Bandung, 2024)
Educational planning constitutes a pivotal element in the endeavor to elevate the quality of education on a global scale. This article analyzes recent advancements in educational planning based on the ideas of Philip H. Coombs, encompassing theory, implementation, and future vision. The present study employs a literature review to explore Parts 4, 5, and 6 of What is Educational Planning, emphasizing the importance of systematic and collaborative approaches. The analysis indicates that intensive training for stakeholders and ongoing research is essential for translating theory into practice. Furthermore, the evaluation of performance systems and the adjustment of educational goals are imperative to ensure the relevance and effectiveness of educational systems. The findings of this study underscore the necessity for innovation and adaptability in educational planning to address future challenges